Mujeres militantes en el movimiento de Derechos Humanos de Argentina. El caso Tucumán - Rubén Isidoro Kotler (Amnis)
This paper aims to analyze some characteristics of de Human Right movement of Tucumán (Argentina) stressing the militancy of women in those organizations, based on the testimonies of: Laura Figueroa, Lawyer of Human Right causes and former Lawyer at the “Asociación de Abogados por los derechos humanos”, an organization that have a short but an intense participation on de movement at the first transition years to the democracy; Sara Mrad, the main leader of “Madres de Plaza de Mayo” in Tucumán since 1981 until now; Ángela Nassif, Historical leader of Communist Revolutionary Party in Tucumán and one of de “Asamblea por los Derechos Humanos” founder’s in this province in 1984, and finally Josefina Centurión, activist in H.I.J.O.S. Tucumán.